A COMPARISON OF THE THERMODYNAMICS OF METAL ADSORPTION ONTO TWO COMMON BACTERIA - Daughney C.J.; Fein J.B.; Yee N. (My University, 1998)
The cell walls of bacteria are known to adsorb a variety of metals, and thus they may control metal mobilities in many low-temperature aqueous systems. In order to quantify metal adsorption onto bacterial surfaces, recent studies have applied equilibrium thermodynamics to the specific chemical and electrostatic interactions occurring at the solution-cell wall interface. However, to date, few studies have used this approach to compare the surface properties and metal affinities of different species of bacteria. In this study, we use acid-base titrations to determine the concentrations and deprotonation constants of specific surface functional groups on Bacillus licheniformis. The cell wall displays carboxyl, phosphate and hydroxyl surface functional groups, with pKa values and 1s errors of 5.2+/-0.3, 7.5+/-0.4 and 10.2+/-0.5, respectively. We perform metal-B. licheniformis adsorption experiments using Cd, Pb, Cu and Al. The average log K values for the Cd-, Pb-, Cu- and Al-carboxyl stability constants, with 1s errors, are 3.9+/-0.5, 4.6+/-0.3, 4.9+/-0.4 and 5.8+/-0.3, respectively. Finally, we compare the surface characteristics and metal affinities of B. licheniformis to those of Bacillus subtilis, as determined by Fein et al. [Fein, J.B., Daughney, C.J., Yee, N., Davis, T., 1997. A chemical equilibrium model of metal adsorption onto bacterial surfaces. Geochim. Cosmochim. Acta 61, 3319-3328]. Our investigations indicate that these two species of bacteria have different relative and absolute concentrations of surface sites and slightly different deprotonation and metal adsorption stability constants. We relate these variations in surface properties to variations in metal affinity in order to predict metal mobilities in complex, natural systems.
Keywords: BACTERIA; METAL; ADSORPTION; COMPARISON